Analysis of child injury surveillance in Tongzhou district of Beijing from 2006 to 2010. (7th October 2012) - Shao, C; Jia, W; Chang, X
Abstract : Background: Now, in China, injury has been become the leading cause of death of children aged 0–14 instead of malnutrition and infectious diseases. Each year, it is estimated that at least 10 million children have been harmed by the various injuries, 100 000 children death and 400 000 children disabled. Objective: To study the status of child injure in Tongzhou district of Beijing for providing scientific basis on injury prevention and control. Methods: Injury surveillance data of three hospitals in Tongzhou district from 2006 to 2010 were collected and analysed. Results: A total of 4855 child injury cases were collected, including 3177 boys (65.42%) and 1679 girls (34.58%). The most frequent time of injury occurrence was June and July in 1 year, and at 10:00 in 1 day. The five main causes of injury were falls (37.72%), animal injury (29.26%), blunt injury (12.68%), non-motor vehicle accident (6.45%) and knife/sharp injury (6.22%). The majority of injuries happened in home (49.42%), schools (25.58%), roads (14.68%), public places (6.49%) and sport facilities (1.69%). Upper limbs (35.61%), lower limbs (32.33%) and heads (23.54%) were injured more frequently than other parts of the body. The most of the injuries are unintentional, minor injuries. Significance: It is suggested to take intervention programmes against different child injuries and increase the publicity of injury in families and schools to improve the supervision of parents and the whole society.